NbWRKY40 Positively Regulates the Response of Nicotiana benthamiana to Tomato Mosaic Virus via Salicylic Acid Signaling - Jiang, Yaoyao; Zheng, Weiran; Li, Jing; Liu, Peng; Zhong, Kaili; Jin, Peng; Xu, Miaoze; Yang, Jian; Chen, Jianping (Frontiers in Plant Science, 2021)
WRKY transcription factors play important roles in plants, including responses to stress; however, our understanding of the function of WRKY genes in plant responses to viral infection remains limited. In this study, we investigate the role of NbWRKY40 in Nicotiana benthamiana resistance to tomato mosaic virus (ToMV). NbWRKY40 is significantly downregulated by ToMV infection, and subcellular localization analysis indicates that NbWRKY40 is targeted to the nucleus. In addition, NbWRKY40 activates W-box-dependent transcription in plants and shows transcriptional activation in yeast cells. Overexpressing NbWRKY40 (OEWRKY40) inhibits ToMV infection, whereas NbWRKY40 silencing confers susceptibility. The level of salicylic acid (SA) is significantly higher in OEWRKY40 plants compared with that of wild-type plants. In addition, transcript levels of the SA-biosynthesis gene (ICS1) and SA-signaling genes (PR1b and PR2) are dramatically higher in OEWRKY40 plants than in the control but lower in NbWRKY40-silenced plants than in the control. Furthermore, electrophoretic mobility shift assays show that NbWRKY40 can bind the W-box element of ICS1. Callose staining reveals that the plasmodesmata is decreased in OEWRKY40 plants but increased in NbWRKY40-silenced plants. Exogenous application of SA also reduces viral accumulation in NbWRKY40-silenced plants infected with ToMV. RT-qPCR indicates that NbWRKY40 does not affect the replication of ToMV in protoplasts. Collectively, our findings suggest that NbWRKY40 likely regulates anti-ToMV resistance by regulating the expression of SA, resulting in the deposition of callose at the neck of plasmodesmata, which inhibits viral movement.